Pemodelan Tegangan Lebih Disebabkan Sambaran Petir Menggunakan Arrester IEEE Dengan Aplikasi ATP-EMTP Pada Studi Kasus Di Nias - Mutiara S. Simanjuntak; Aprima Anugerah Matondang; Juanto Simangunsong (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Lightning has always been a dangerous threat to the equipment of electric power systems consisting of: power plants, substations, transmission lines and distribution lines. Generally, overhead high-voltage transmission lines are exposed to lightning strikes. Therefore, the degree of protection against lightning is determined based on the degree of insulation of the equipment. To prevent damage to equipment due to lightning strikes, arresters are used. In this study, three arrester models were used as comparisons, namely. IEEE arrester model. The system was simulated using Alternative Transients Program (ATP) software. The results showed that the lightning rod was declared successful in protecting the transmission system, where the three lightning rods had a Margin Protection (MP) of arresters that reached 28%. In the simulation, it is known that the IEEE arrester successfully cut off the lightning current in the transmission system so that the transient overvoltage recorded on the transformer does not exceed the Basic Insulation Level ((BIL) trafo.